الضرر العضلي بدلالة بعض المؤشرات البايوكيميائية و علاقتة بفاعلية الاداء لملاكمي الاوزان الخفيفة - الفؤادي, قيس سعيد دايم (Sulaimani Journal for Humanities, 2018)
The game of boxing games characterized by friction between the players directly and very influential nature of the game requires scoring points on the number of times the opponent directly hit by the amount of areas allowed in the law does not directly affect the muscles that are targeted and also causing harm Muscular in them. The game is under the anaerobic an aerobic power system and the players practice in attacking and defense to protect points scoring areas as well as attacking the points scoring areas on the opponent and to study this topic, the extent of muscle damage Which affects the players because of direct contact and knowledge of the relationship and its relationship to training and competitions Arte researcher to delve into this problem and study some indicators of muscle damage biochemical as well as the effectiveness of the performance of boxers during the games and therefore possible to point out vinegar Whether they were to increase signs of muscular damage or poor performance of players in offensive defense.